Fuzzy reliability theory analysis of traffic signal lamp performance - Mason D. Gemar; Shidong Pan; Zhanmin Zhang; Randy B. Machemehl (Multimodal Transportation)
Over the past decade, many municipalities have begun to replace incandescent lamps in their traffic signals with light emitting diode (LED) arrays. While LED technology boasts longer lifetimes and superior performance over their counterparts, there are many limitations involved in both testing and evaluating their reliability. As such, the methodology and subsequent analysis procedures used to evaluate the reliability of traffic signal lamps along a corridor is proposed. To accomplish this task, the progression of the reliability assessment from individual lamp to the entire signal light system for a corridor is demonstrated. Furthermore, due to the nature of these systems and reliability assessment strategies, it is suggested that fuzzy, or more specifically, profust reliability theory could be applied to effectively analyze LED arrays, as well as corridor-wide signal light systems. Preliminary case study results, coupled with field observations of partially burned-out LED arrays, support this hypothesis.